2021
DOI: 10.1177/17455065211063021
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of HIV seropositivity to sexual partner in Ethiopia: A systematic review

Abstract: Introduction: In Ethiopia, the burden of HIV/AIDS is a public health issue that requires significant control of transmission. Once an infection has been established, determinants influence people living with HIV to disclose or not their HIV-positive status to sexual partners. This study assessed the proportion and associated factors of people living with HIV’s disclosure status to sexual partners. Methods: CRD42020149092 is the protocol’s registration number in the PROSPERO database. We searched PubMed, Scopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
1
4
1
Order By: Relevance
“…Our findings support previous studies conducted in Togo ( 93 ) and Uganda ( 94 ). On the contrary, our HIV disclosure rate was lower than in the United States ( 95 ), and some African countries, such as Kenya ( 96 ), South Africa ( 97 ), Ethiopia ( 31 ).…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…Our findings support previous studies conducted in Togo ( 93 ) and Uganda ( 94 ). On the contrary, our HIV disclosure rate was lower than in the United States ( 95 ), and some African countries, such as Kenya ( 96 ), South Africa ( 97 ), Ethiopia ( 31 ).…”
Section: Discussioncontrasting
confidence: 74%
“…They focused on influencing factors of HIV disclosure ( 14 , 20 22 ), disclosure policies and their effectiveness ( 13 , 23 , 24 ), interventions for HIV disclosure ( 25 , 26 ), evaluation of self-report disclosure tools ( 27 ), and the HIV disclosure among specific populations such as adolescents or immigrants ( 28 30 ). Four reviews synthesized the proportions of HIV partner disclosure among Ethiopian adults with PDWH ( 31 34 ). One ( 31 ) reported 76.03% of pooled disclosure rate (18 studies, 8,009 participants), while the other ( 32 ) reported 73% of disclosure rate (12 studies, 4,528 participants).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the fear of being avoided and judged is still highly reported. A similar prevalence was reported by Endalamaw et al in Ethiopia (76%) [28], while a lower rate of disclosure resulted from a systematic review conducted in China (65%) [29]; however, both studies considered disclosure to sexual partners only and come from very different contexts [28,29]. An observational study conducted in 2012 and 2013 aiming to assess disclosure attitudes and predictors among women living with HIV reported a high prevalence of disclosure (1724/1929, 89%); women from Western Europe showed better attitudes towards disclosure, data that we hope has improved since the spreading of the U=U campaign [30].…”
Section: Discussionsupporting
confidence: 90%